Delving into the Spoken English of T’boli ESL Learners: A Descriptive Study - Barcibal, Remar B.; Abaigar, Caroline L.; Lemana II, Henry E. (Future Science / FSH-PH Publications, 2023)
A culturally pluralistic country, the Philippines has more than a hundred spoken languages used on national, regional, and local scales. With this abundant number, studies on English as a second language acquisition by many indigenous people have remained scarce over the years. To attempt to address the lacuna, this qualitative study aimed to describe the spoken English of the T’bolis at the word and sentential levels. The participants of the study were 20 senior high school T’boli students at one private school in the Municipality of T’boli, South Cotabato. They were asked to read an English newspaper article, and recordings of the utterances were transcribed and analyzed through structured guides. Based on the findings, the participants exhibited dominant features in their spoken English, like replacing vowels and consonant sounds; substituting and omitting sounds when articulating words; shifting the stress of a syllable of a word; not pausing before and after a parenthetical expression and after a thought group; using falling intonation in unfinished statements; and using rising tone in the second syllable of words that are not considered important in a statement. While the findings of this study served as bases for understanding the dominant features of the T’boli spoken English, they do not necessarily reflect the distinction of their spoken English among other non-native English speakers. The study then implies that there is a need to understand the English communication skills of T’bolis, the idiosyncrasies of their native language, and other factors that affect how they learn English.